Extensive MHC class IIβ diversity across multiple loci in the small-spotted catshark (Scyliorhinus canicula) - Arnaud Gaigher; Alessia Rota; Fabiana Neves; Antonio Muñoz-Mérida; Javier Blasco-Aróstegui; Tereza Almeida; Ana Veríssimo (Scientific Reports, 2023)
Abstract The major histocompatibility complex (MHC) is a multigene family responsible for pathogen detection, and initiation of adaptive immune responses. Duplication, natural selection, recombination, and their resulting high functional genetic diversity spread across several duplicated loci are the main hallmarks of the MHC. Although these features were described in several jawed vertebrate lineages, a detailed MHC IIβ characterization at the population level is still lacking for chondrichthyans (chimaeras, rays and sharks), i.e. the most basal lineage to possess an MHC-based adaptive immune system. We used the small-spotted catshark (Scyliorhinus canicula, Carcharhiniformes) as a case-study species to characterize MHC IIβ diversity using complementary molecular tools, including publicly available genome and transcriptome datasets, and a newly developed high-throughput Illumina sequencing protocol. We identified three MHC IIβ loci within the same genomic region, all of which are expressed in different tissues. Genetic screening of the exon 2 in 41 individuals of S. canicula from a single population revealed high levels of sequence diversity, evidence for positive selection, and footprints of recombination. Moreover, the results also suggest the presence of copy number variation in MHC IIβ genes. Thus, the small-spotted catshark exhibits characteristics of functional MHC IIβ genes typically observed in other jawed vertebrates.